2004
DOI: 10.1007/s11661-004-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a thermal model of the direct chill casting of AZ31 magnesium billets

Abstract: A mathematical model of the direct chill (DC) casting process for magnesium billets has been developed to predict the temperature in the billet, dummy block, and center pin using the commercial finiteelement (FE) package, ABAQUS. Boundary conditions used for primary and secondary cooling and interfacial cooling between the billet and dummy block were defined based on the literature and knowledge of the physical phenomena occurring during the process. Temperatures in the billet, mold, and dummy block, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Hot tears are thought to occur as a result of the development of tensile strains in the casting at high fraction solid (fs) due to temperature gradients and/or mechanical constraints [3], in combination with limited liquid feeding [4] and low ductility [5]. In recent years, a number of mathematical models [6][7][8] have been developed to quantify the influence of casting parameters on the development of semi-solid thermal stresses and strains, in an effort to reduce solidification defects. These models require prior knowledge of the magnesium constitutive behaviour in the as-cast state over a wide range of temperatures and strain rates.…”
Section: Paper Textmentioning
confidence: 99%
“…Hot tears are thought to occur as a result of the development of tensile strains in the casting at high fraction solid (fs) due to temperature gradients and/or mechanical constraints [3], in combination with limited liquid feeding [4] and low ductility [5]. In recent years, a number of mathematical models [6][7][8] have been developed to quantify the influence of casting parameters on the development of semi-solid thermal stresses and strains, in an effort to reduce solidification defects. These models require prior knowledge of the magnesium constitutive behaviour in the as-cast state over a wide range of temperatures and strain rates.…”
Section: Paper Textmentioning
confidence: 99%
“…The application of the heat transfer model was based on the following assumptions [7][8][9] : 1) Some properties depend on temperature. The values of conductivity and specific heat and other properties are independent on the space.…”
Section: Methodsmentioning
confidence: 99%
“…Tests on the casting of magnesium-based alloys [20] showed that casting speed has a large impact on the pool depth. As casting velocity is increased, the metal pool deepens.…”
Section: Casting Velocitymentioning
confidence: 99%